Resource Orchestration in Enhancing Green Innovation and Environmental Performance in SME - Rustiarini, Ni Wayan; Bhegawati, Desak Ayu Sriary; Mendra, Ni Putu Yuria; Vipriyanti, Nyoman Utari (International Journal of Energy Economics and Policy, 2023)
Economic growth has led to global environmental gradation and made environmental issues the main agenda in current business practices, including SMEs. Referring to the Resource Orchestration Theory, this study uses a new approach that conducts internal resource orchestration to implement green practices in SMEs. This study aims to identify the role of green intellectual capital and green transformational leadership in enhancing green innovation and environmental performance. The survey was conducted on the woodcraft industry located in Bali, Indonesia. Research data were analyzed using Partial Least Square. The research results prove that green intellectual capital significantly increases green innovation and environmental performance. Meanwhile, green transformational leadership only increases green innovation, but it is not proven to improve environmental performance significantly. The findings also confirm that green innovation is a mediating variable in the relationship between green innovation, green transformational leadership, and environmental performance.